2001
DOI: 10.1038/sj.bmt.1703137
|View full text |Cite
|
Sign up to set email alerts
|

A phase II trial evaluating the safety and effectiveness of the AastromReplicell system for augmentation of low-dose blood stem cell transplantation

Abstract: Summary:To reduce the number of apheresis procedures and maintain the usual rate of hematopoietic recovery in patients treated with high-dose chemotherapy, we studied the effect of adding a small volume of ex vivo expanded bone marrow to low doses of CD34 + blood stem cells. Thirty-four patients with breast cancer received G-CSF (10 g/kg/day) priming followed by a limited volume (50-100 ml) bone marrow aspiration and standard 10-liter aphereses. Marrow was expanded ex vivo using the AastromReplicell system and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Recent laboratory and clinical trials have demonstrated more effective approaches in eliminating contaminating malignant cells from marrow and blood stem cell products using chemical agents, monoclonal antibodies, CD34 + affinity devices, ex vivo expansion, and other techniques [20,[28][29][30][31][32][33][34]. Thus, the importance of blood stem cell product contamination may increase with improvements in eradication of in vivo residual disease in patients with metastatic breast cancer treated with high-dose chemotherapy [30].…”
Section: B B and M Tmentioning
confidence: 99%
“…Recent laboratory and clinical trials have demonstrated more effective approaches in eliminating contaminating malignant cells from marrow and blood stem cell products using chemical agents, monoclonal antibodies, CD34 + affinity devices, ex vivo expansion, and other techniques [20,[28][29][30][31][32][33][34]. Thus, the importance of blood stem cell product contamination may increase with improvements in eradication of in vivo residual disease in patients with metastatic breast cancer treated with high-dose chemotherapy [30].…”
Section: B B and M Tmentioning
confidence: 99%
“…The proprietary Replicell technology developed by Aastrom Biosciences Inc. was shown to be feasible but not definitively effective in enhancing myeloid, erythroid or platelet engraftment in the clinical setting (Jaroscak et al, 2003, Pecora et al, 2001. The system uses stromal co-cultures while also providing a continuous supply of culture medium containing fetal calf serum, horse serum, PIXY321 (a GM-CSF/IL-3 fusion protein), flt3 (FL) and erythropoietin (EPO) (Stiff et al, 2000).…”
Section: Preclinical and Clinical Studies Using Cord Blood Hscmentioning
confidence: 99%
“…This technology results in significant expansion of primary human cells 20,21 and has previously demonstrated clinical success in the expansion of bone marrow and blood cells for replenishment of hematopoietic cells after treatment of various blood dyscrasias. [22][23][24][25] Additionally, results of recent in vitro and in vivo studies have generated interest in using this process to produce cells for bone tissue regeneration. 26 The hypothesis underlying the current study is that BRCs have osteogenic and angiogenic potential that could manifest in their ability to regenerate bone and vascular tissue in a clinical craniofacial application.…”
Section: Introductionmentioning
confidence: 99%